Contribuições da teoria histórico-cultural para a utilização das tecnologias digitais na educação infantil - Godoi, Nayara Elias Pinheiro (2022)
This dissertation comes from the Professional Master's Stricto Sensu of the Graduate Program in Teaching in Basic Education of the Center for Teaching and Research Applied to Education at Federal University of Goiás, Goiânia, GO and is linked to the line of research Theoretical-Methodological Conceptions and Teaching Practice. For this, empirical research had been accomplished from continuing education in service with two teachers of Early Childhood Education in the city of Santa Helena de Goiás. The research problem has presented as follows: What elements of the Historical-Cultural Theory can contribute to the teacher's pedagogical action when using digital technologies in Early Childhood Education? To answer this question, the general objective was elaborated: to analyze, from the study of some elements of THC, the possible contributions of this theory in the realization of the pedagogical action of teachers when using digital technologies in EI. The qualitative approach supported the performance of each stage, which had THC as a theoretical assumption that guided the discussion of the elements that underlie the didactic-pedagogical organization for the use of digital technologies in Early Childhood Education. Theoretical studies had been accomplished on aspects related to the use of technologies in training spaces and, for this, we used Peixoto (2012; 2015), Peixoto and Araújo (2015), Sancho (2006), and Nascimento (2014). The authors who supported the discussion on Early Childhood Education were Barbosa (2010; 2013), Raupp and Arce (2012), Sousa (2013), Sousa and Cruz (2020), and on Historical-Cultural Theory (THC), were Vygotsky (1991); 2005), Leontiev (1978), Fichtner (2010), Libâneo (2004, 2012, 2014), Mello (2007; 2015), Freitas (2007), Pino (2000) among others. The production of data occurred through/from descriptions and reflections recorded in the logbook, from the writings of the participating teachers related to the guiding activities of the studies, participation in training meetings, as well as the data apprehended in the questionnaire, in the semi-structured interview and the recording in video and audio during the training. By analyzing the data, we developed the educational product "The use of digital technologies in Early Childhood Education: Contributions from elements of the Historical-Cultural Theory", in the form of an ebook. It was written, based on the reflection that the pedagogical use of digital technologies in educational spaces, must be intentionally planned from a pedagogical theoretical basis. In this way, it is presented as support material for teachers who work at this stage of basic education, contributing to their initial and/or ongoing training. If in-service continuing education allowed teachers to re-signify their practice by reflecting on aspects related to conceptions of education, Early Childhood Education, and the teacher's role in the process of training young children. Referred to the child and its teaching and learning process, as well as in the reflections r carried out on the form of organization and planning of pedagogical practice, using or not technology as a resource.